Cache strategies for internet-based video on-demand distribution - Moreira, Josilene Aires (2011)
Aires Moreira, Josilene; Fawzi Hadj Sadok, Djamel. Cache strategies for internet-based video on-demand distribution. 2011. Tese (Doutorado). Programa de Pós-Graduação em Ciência da Computação, Universidade Federal de Pernambuco, Recife, 2011.